The Other Side of Sexting: Relationship between Perspective and Victimization - Ergüll, Dila; Ziyalar, Neylan (The Bulletin of Legal Medicine, 2022)
Objective: Sexting is emerged as a result of the frequent use of internet and social media to send messages, photos and videos quickly and easily and it became a common concept nowadays. In this sense, the aim of the study is to determine the factors which affects the perspective towards sexting and to investigate whether there is a relationship between victimization and sexting.Methods: The sample of this research is consisted of 565 participants who are ≥18 years. Theory of Reasoned Action has been used as a background theory to predict and determine the perspective towards sexting and sexting behaviour. The data were collected by using demographic information form and sexting scale which are prepared by researchers.Results: It was determined that a great majority of the participants engaged in sexting, men had more positive attitude and more frequent behaviour compared to women, and being a victim of sexting did not make a significant difference on the perspective towards sexting. The proportion of individuals who became a victim because of sexting is 22.5% and most of them were women. According to  types of victimization, individuals mostly experience emotional and psychological problems; however, it has been determined that the victimization is not limited to a single form.Conclusion: The prevalence of sexting, perspectives of the individuals and their motivation to act are determined to a certain extent. In this way, the case of unconsidered sexting in Türkiye is identified and it is asserted  that it can cause serious problems worth considering.
Keywords: Sexting; Victimization; Theory of reasoned action